An Investigation of Alternative Assessment for writing skill in second semester of Industrial Engineering at University of Muhammadiyah Gresik - Rizqiyah, Dwi Masyithah; Asmara, Candra Hadi (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
Assessment has various types in education program. Even, it was as one of aspect in determining the students’ skill. Additionally, one skill which is as the last skill in language acquisition is writing. Since it is the last, means it is difficult to be learnt moreover to be assessed. When writing is difficult to be assessed, the teacher has to know and understand various type of assessment for writing. This study was conducted to describe types of alternative assessment for writing skill in 2nd semester of Industrial Engineering at University of Muhammadiyah Gresik in academic year of 2016/2017 and also to describe implementation of Alternative Assessment for writing skill in second semester of Industrial Engineering at University of Muhammadiyah Gresik which used descriptive qualitative. There were two lecturers of D1 English Language at UMG who were as the subject of this study which were selected by questioners about the alternative assessment for writing skill. The data collected by observation in K and L classes of Industrial Engineering Department. Additionally, the interview was done with two lecturers and some students. The finding of this study showed that two lecturers applied alternative assessment with same type. Those were writing sample, conference, and teacher- feedback. Furthermore, the implementation of alternative assessment in writing skill was done by asking and drill the students in composing writing to make them comprehend about writing composition and be more confident for composing writing. After they comprehended then they could compose full text. When the students practice in writing, the lecturer guided them by discussing face to face or in whole class. The feedback had to be given to develop the students’ motivation in writing. When the motivation was high then the students could improve their writing composition and help the students to revise their writing’ work. It can be concluded that alternative assessment for writing skill which have been applied are writing sample, conference, and teacher-feedback. The writing sample uses as the practice by composing sentence then compose text to know the progress. The conference can be held in face to face with lecturer and with whole class. Additionally, the feedback can be given during activity and after activity in spoken and written by directly or indirectly. The researcher suggests the further researcher to conduct at another level. The researcher hopes that there will be further research on the implementation of alternative assessment for writing skill in different field or study with different subject and different focus.